Advances in epigenetic mechanisms of lead toxicity - ZHANG Xinxin; YAN Chonghuai (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Lead is a ubiquitous toxic heavy metal and one of the earliest and most widely used heavy metal elements in human history. Due to its non-degradable nature in the environment and its long biological accumulation effects (lasting up to 30‒50 years) in the human body, even trace amounts of lead can cause significant health damage. It has therefore been classified as one of the top ten public health concerns by the World Health Organization (WHO). Once absorbed into the body, lead is typically distributed in tissues such as the brain, liver, kidneys, teeth, and bones, thereby exerting widespread toxic effects on multiple organ systems. Epigenetics is the study of heritable changes in gene expression that occur without alterations in the nucleotide sequence. It reveals how modifications in gene expression regulate cellular functions, leading to diverse cellular phenotypes and functions despite identical DNA sequences. Although the toxic mechanisms of lead are not yet fully elucidated, recent studies suggest that epigenetic regulation may play a significant role in mediating lead toxicity. Environmental lead exposure can induce various epigenetic modifications in cells, such as DNA methylation, histone modifications, and microRNA (miRNA) alterations, which, in turn, can trigger multiple toxic responses. This paper presents a concise overview of current epigenetic investigations into lead toxicity, emphasizing DNA methylation, histone modifications, and miRNA dynamics. By adopting an epigenetic perspective, it offers a theoretical framework into understanding lead's toxic mechanisms comprehensively, facilitating further research in prevention and treatment strategies.